2020
DOI: 10.1111/jcmm.15693
|View full text |Cite
|
Sign up to set email alerts
|

SRXN1 stimulates hepatocellular carcinoma tumorigenesis and metastasis through modulating ROS/p65/BTG2 signalling

Abstract: Sulfiredoxin 1 (SRXN1) is a pivotal regulator of the antioxidant response in eukaryotic cells. However, the role of SRXN1 in hepatocellular carcinoma (HCC) is far from clear. The present study aims to elucidate whether SRXN1 participates in tumorigenesis and metastasis of HCC and to determine the molecular mechanisms. We found that SRXN1 expression was up‐regulated in HCC tissue samples and correlated with poor prognosis in HCC patients. We also observed that SRXN1 knockdown by transient siRNA transfection inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Sulfiredoxin 1 (SRXN1) acts as a key factor regulating the antioxidant response in eukaryotic cells, can resist oxidative stress injury in cells and has antioxidant protective effects on many diseases [ 32 ]. The findings of Lv [ 33 ] demonstrated that SRXN1 modulated ROS/p65/BTG2 signaling, thereby stimulating HCC tumorigenesis and metastasis. Lactate dehydrogenase A (LDHA) serves as an important metabolic enzyme that is a member of the family of 2-hydroxy acid oxidoreductases and remarkably affects the anaerobic metabolism of cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfiredoxin 1 (SRXN1) acts as a key factor regulating the antioxidant response in eukaryotic cells, can resist oxidative stress injury in cells and has antioxidant protective effects on many diseases [ 32 ]. The findings of Lv [ 33 ] demonstrated that SRXN1 modulated ROS/p65/BTG2 signaling, thereby stimulating HCC tumorigenesis and metastasis. Lactate dehydrogenase A (LDHA) serves as an important metabolic enzyme that is a member of the family of 2-hydroxy acid oxidoreductases and remarkably affects the anaerobic metabolism of cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, by reducing ROS and affecting apoptosis, Srx may favor the survival of cancerous cells and thereby contribute to carcinogenesis [ 48 ]. For instance, Srx underexpression can sensitize cancer cells to ER stress-induced cell death [ 49 ], increase apoptosis of tumor cells and thus decrease tumor cell proliferation, while the opposite effects have been observed in Srx overexpressors, which correlated with more aggressive cancers and poor prognosis [ 8 , 48 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was confirmed that overexpressed PRDX1 was closely related with poor prognosis of HCC patients 29 . Sulfiredoxin-1 (SRXN1) was revealed a pro-tumorigenic in HCC by regulating ROS signaling 30 . In addition, SRXN1 is involved in oxidoreductase activity 31 , its overexpression may play a crucial role in the tumorigenesis and progression of HCC 32 .…”
Section: Discussionmentioning
confidence: 99%